THE EFFECT OF NaOH CONCENTRATION AND TEMPERATURE ON ZEOLITE SYNTHETIS FROM FLY ASH BY HIDROTHERMAL ALKALI - Jumaeri, Jumaeri; Sutarno, Sutarno; Kunarti, Eko Sri; Santosa, Sri Juari (Jurnal Zeolit Indonesia, 2009)
Zeolite synthesis from coal fly ash PLTU Tanjung Jati Japara was conducted by hydrothermal alkali. Preparation was done on fly-ash that has been refluxed with 1M of HCl and without refluxed. NaOH with certain concentration (2, 3, and 4M) was mixed with coal fly-ash by ratio 10 ml each 1 gram of fly ash into Teflon tube 100 ml at autoclave stainless-steel. Then, autoclave was heated on the oven at temperature of 120-1600C. Synthetic zeolite ouput was qualitative tested by using infrared spectroscopy, X-Ray diffraction, and SEM. The result showed that NaOH concentration, temperature, and hydrothermal alkali period of coal fly ash was affecting characterization of zeolite ouput. The temperature which use for optimally hydrothermal processes exist on range 140 â160oC. The increase of temperature causes improving crystallization of zeolite products. Hydrothermal synthetic product from fly ash is alumina-silica compound which are a mixture of some crystals such as P zeolite, Y zeolite, sodalite, mullite, and quartz.